Six Months of Piano Training in Healthy Elderly Stabilizes White Matter Microstructure in the Fornix, Compared to an Active Control Group - Jünemann, Kristin; Marie, Damien; Worschech, Florian; Scholz, Daniel S.; Grouiller, Frédéric; Kliegel, Matthias; Van De Ville, Dimitri; James, Clara E.; Krüger, Tillmann H. C.; Altenmüller, Eckart; Sinke, Christopher (Frontiers in Aging Neuroscience, 2022)
While aging is characterized by neurodegeneration, musical training is associated with experience-driven brain plasticity and protection against age-related cognitive decline. However, evidence for the positive effects of musical training mostly comes from cross-sectional studies while randomized controlled trials with larger sample sizes are rare. The current study compares the influence of 6 months of piano training with music listening/musical culture lessons in 121 musically naïve healthy elderly individuals with regard to white matter properties using fixel-based analyses. Analyses revealed a significant fiber density decline in the music listening/ musical culture group (but not in the piano group), after 6 months, in the fornix, which is a white matter tract that naturally declines with age. In addition, these changes in fiber density positively correlated to episodic memory task performances and the amount of weekly piano training. These findings not only provide further evidence for the involvement of the fornix in episodic memory encoding but also more importantly show that learning to play the piano at an advanced age may stabilize white matter microstructure of the fornix.